Pembangunan dasar pertahanan komprehensif : Kajian ke atas dasar pertahanan negara (1986-2010) - Muhamad Saifulbakri, Yusoof (2021)
Malaysia has its own National Defence Policy (NDP) since 1957 in order to handle the nation’s security issues. The NDP developed aims to ensure that Malaysian Armed Forces (MAF) has the readiness in facing any internal or external threats. Since 1990 after the Cold War era, the efforts to modernise MAF have been actively done by the government in line with the non-traditional threats that started to roam around the security issues which impacted the national interests. Although NDP and MAF have gone through a few phases of developments and modernisations, there are still security issues that resulted in MAF’s abilities and NDP’s capabilities being questioned by many parties. These issues include the terrorist attack in Lahad Datu, the disappearance of MH370, MAF outdated and dysfunctional logistics problems and a few other issues. It is common knowledge that, apart from the defence strategy, the NDP also outlines the concept of defence to make the country's defence system better in the face of non-traditional threats today. However, it is still seen weak when there are various problems encountered during the implementation of the NDP. The weaknesses of the NDP can be assessed based on several important components such as logistics issues, defence industry, Military Affairs (RMA), financial resources and defence strategy. Through qualitative method, this study was conducted to identify the factors that influence the development of the Malaysia’s NDP, to identify the main components in the NDP, to analyze the problems and effects of the NDP and to identify prospect to formulate a comprehensive NDP. On the basis of the qualitative analysis that has been conducted, the study found various problems that occur in the components of the DPN. This shows that the aspect of the nation’s defence is very weak and MAF developed by the Malaysian government is not a comprehensive policy as well as causing the MAF defence capability not being in line with the dynamic nature of threat at present.